PROPOSTAS PARA O ENSINO DA TRIGONOMETRIA:INTRODUÇÃO À APROXIMAÇÃO DE FUNÇÕES PERIÓDICAS POR POLINÔMIOS TRIGONOMÉTRICOS - Iochucki, Suellen Karina Palhano (2016)
This work presents an approach to trigonometry content using Geogebra and Maxima programs. It provides a road map of how trigonometry can be worked in the classroom divided into stages . It proposes applications of trigonometry in different areas of knowledge and suggests the introduction of the approach of periodic functions by trigonometric polynomials . It is a qualitative and exploratory research . Its relevance is justified because it allows the teacher to look at the process of teaching and learning significantly to the student. During the development of research, the approach of trigonometry content was the history of mathematics and the use of software. The use of computing resources was an important ally to scientific knowledge, as well as the use of applications for the contextualization.